Catalogue of the ants (Hymenoptera: Formicidae) of Bulgaria - Albena Lapeva-Gjonova; Vera Antonova; Alexander Radchenko; Maria Atanasova (ZooKeys, 2010)
The present catalogue of the ants (Hymenoptera, Formicidae) of Bulgaria is made on a base of critical reconsideration of literature (covering the period from 1892 till 2009 and part of 2010) as well as on examination of the authors‘ and several museum‘s collections. A lot of data were omitted in the previous Bulgarian monograph on ants, lots of new data were recently added and many important additions and alterations were made due to taxonomic revisions of Eurasian Formicidae during the last three decades. Two new species are reported for the country [Temnothorax graecus (Forel, 1911) and Temnothorax cf. korbi (Emery, 1924)]. This catalogue contains a list of 163 ant species belonging to 40 genera of 6 subfamilies now known from Bulgaria. Synonyms and information on the previously reported names in relevant publications are given. Known localities of the species are grouped by geographic regions. Maps with concrete localities or regions for each species were prepared. The conservation status of 13 ant species is given as they are included in IUCN Red List of Threatened Species and Bulgarian Biodiversity Act. In comparison with adjacent Balkan regions the ant fauna of Bulgaria is quite rich and its core is composed of South European elements.